HEARING SCREENING IN A GROUP OF PAEDIATRIC PATIENTS ATTENDING AN HIV/AIDS CLINIC: A PILOT STUDY - Khoza-Shangase, Katijah; Turnbull, Taryn (African Journal of Infectious Diseases (AJID), 2009)
The aim of this investigation is to screen hearing function in a group of paediatric patients attending a HIV/AIDS clinic at a hospital in Gauteng, South Africa. There is a dearth of published research in this area, particularly from developing countries. A total of 62 paediatric patients attending a virology clinic at a teaching hospital in Johannesburg participated in the study. The sample included both males and females from ages 18 months to 6 years. An exploratory descriptive, non-experimental and observational design with no control group and non-randomization of participants was used. The participants’ age and medical history were the independent variables, while the audiological tests (otoscopy, tympanometry & otoacoustic emissions) were the dependant variables. Audiological measures that included case history and medical record reviews, otoscopic examination, immittance, as well as otoacoustic emissions testing were conducted on participants. After completing the test measures, each participant was classified as having either pass or refer screening findings. A closer descriptive analysis was then conducted of the participants who presented with refer findings. Both qualitative and quantitative analysis of the data was performed. The estimated prevalence of abnormal hearing screening results among the participants assessed was found to be 26% in the current study. These findings were found at the various stages of the disease, and the symmetry, estimated type and degree of the auditory dysfunction was variable. Furthermore, otitis media was found to be prevalent in 23% of participants and was the most prevalent possible cause of hearing loss in the sample evaluated. These findings highlight the need for audiologists and otolaryngologists’ involvement in the assessment and management of this population.